Morbimortalidade por câncer colorretal e fatores associados em uma unidade federativa da Amazônia Legal - Caló, Romero dos Santos (2021)
Worldwide, about 18.1 million people became ill with cancer in the year 2018, and another 29.5 million people will be diagnosed with cancer by 2040, and colorectal cancer (CRC) has been one of the types of cancer that most contributed to the morbidity and mortality of the disease, in both sexes, worldwide. As cancer is a multifactorial disease, it is important that studies are undertaken to identify the factors associated with the burden of different types of disease. Objective – To analyze morbidity and mortality from colorectal cancer and associated factors in a federative unit of the Legal Amazon, from 2000 to 2016 (general). To analyze the trend of incidence of CRC, according to sex and age group, in Greater Cuiabá, state of Mato Grosso, from 2000 to 2016 (manuscript 1). To analyze the correlation between CRC mortality rates and socioeconomic factors in the Intermediate Geographic Regions (RGI) of the state of Mato Grosso, from 2005 to 2016 (manuscript 2). To analyze the temporal and spatial distribution of CRC mortality with pesticide consumption in the state of Mato Grosso, from 2001 to 2016 (manuscript 3). Methods – This is an ecological study, with a descriptive approach. The CRC incidence information came from the RCBP-Cuiabá covering the municipalities of Cuiabá and Várzea Grande (Grande Cuiabá), available on the INCA website. Data on death by CRC were provided by the Mato Grosso State Department of Health and are part of the Mortality Information System. For the identification of CRC cases and deaths, the codes for the disease registered according to the 10th edition of the International Statistical Classification of Diseases and Related Health Problems were considered: C18 (malignant colon neoplasm), C19 (malignant neoplasm of the rectosigmoid junction), C20 (malignant neoplasm of the rectum) and C21 (malignant neoplasm of the anus and anal canal). Incidence and mortality rates were standardized by the direct method, using the world standard population and are reported per 100,000 inhabitants. Mato Grosso has 141 municipalities and 5 RGI (North, Northeast, Southeast, Southwest and Center-South) and information on the number of inhabitants of the study populations was obtained from the Brazilian Institute of Geography and Statistics, from the Demographic Census for the year 2010, and population estimates for the remaining years (inter-census). The covariates used were gender (male and female); age group (30 to 39 years, 40 to 49 years, 50 to 59 years, 60 to 69 years, 70 to 79 years and 80 years or more); general Firjan Municipal Development Index (IFDM), IFDM education, IFDM income and employment and IFDM health, obtained from the Firjan system website; and pesticide consumption, with information obtained from the Institute of Agricultural Defense of Mato Grosso and the IBGE Automatic Recovery System. To analyze the temporal trend of the incidence of CRC, the Joinpoint regression was used. To analyze the correlation between mortality rates from the disease and socioeconomic factors, Pearson's correlation was used. For the analysis of the spatial and temporal distribution of mortality by CRC with pesticide consumption, thematic maps and their respective Kernel intensities were made, as well as the overlapping of environment and health indicators. Results – Manuscript 1: For the state of Mato Grosso, 1,715 cases of CRC were registered, with an overall crude rate of 28.6 new cases/100,000 inhab. and overall adjusted rate of 16.2 new cases/100,000 inhab. Men tended to increase the incidence rates of CRC in the age group 70 to 79 years, with an increase of 4.0% per year, while women tended to increase in the age group 50 to 59 years, with an increase of 2.7% per year. Manuscript 2: There was a significant correlation between mortality rates from the disease with the following indicators: General IFDM for the North, Southeast and Center-South RGI of the state; Education for the North and Southeast RGI; Income and employment for the North and Center-South RGI and Health for the North, Southeast and Center-South RGI. Manuscript 3: An increase in the density of mortality rates was observed, mainly in the center of the state, northeast and southwest. The regions located in the middle north, west and southeast had the highest consumption of pesticides and also the highest standardized rates of mortality by CRC. On the other hand, in the municipalities with the lowest consumption, located in the northern regions of the state, the lowest rates for CRC were found. Conclusion – Men from Greater Cuiabá showed a trend towards an increase in the incidence of CRC more significantly, but in women this occurred in a younger age group. There was a correlation between better socioeconomic development and higher mortality rates due to CRC in the state's RGI. Although evidence of direct association is limited, this study suggests that the consumption of pesticides contributes to the maintenance and increase of mortality rates due to CRC in the state of Mato Grosso.